Pergeseran Nilai Budaya Bimbang Adat Pada Tradisi Pernikahan Di Kecamatan Manna Kabupaten Bengkulu Selatan - Arti, Ferta Juni; Widiastuti, Tuti (UNIVED PRESS, Universitas Dehasen Bengkulu, 2024)
This research aims to obtain data on the shift in cultural values in the customs of marriage traditions in Manna District, South Bengkulu Regency. The research was conducted in Manna District, South Bengkulu Regency for 5 months from August 2023 to December 2023. The method used is a qualitative descriptive method that is carried out through observations, observations, and in-depth interviews with customary heads, village heads, RT/RW and the Community. The results of this study resulted in the existence of a shift in customs that occurred in the Manna community of South Bengkulu Regency along with the development of the times and the progress of science and technology, another thing that makes the shift is a fairly large budget for traditional indecisive processions, making people choose modern or ordinary wedding processions.